Effectiveness of Neem, Garlic and Red Chili Against Adult Dermestid Beetle in Sun Dried Fish (Progressive Agriculture, 2013)
The suitability of neem (Azadirachta indica), garlic (Allium sativum) and red chili (Capsicum frutescens) in repelling insects in dried fish during processing and storage was determined. Their acetone extracts were used to evaluate toxic effects against adult dermestid beetle, Dermestes sp. The concentration of plant extracts were 60%, 80% and 100% for adult Dermestes sp. The LC50 values of neem, garlic and red chili were 1.81%, 4.85% and 1.11%, respectively at 24 hours after treatment (HAT), indicating that red chili was the most toxic plant. Red chili possessed the highest toxic effect at 48 HAT (0.87%) and 72 HAT (0.03%). It was observed that all of the three plant extracts had repellent action on adult Dermestes sp. The highest mean repellency was observed in neem extract (62.67%) followed by red chili (38.44%) and garlic (31.11%). Repellent effects increased with the concentration of plant extracts.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16865 Progress. Agric. 20(1 & 2): 133 142, 2009